The Role of Village Government in Community Empowerment in Medan Estate Village, Percut Sei Tuan District, Deli Serdang District - Aprillia, Vina; Berliana Silalahi, Reni; Juliandi; Hidayat Rastami, Mhd. Ilham; Sabeta Nainggolan, Reni; Ivanna, Julia (Berpusi Publishing, 2023)
The problems experienced by almost all villages in Indonesia are people's welfare and the low economic level of the community. The community empowerment program is an effort to develop the independence and welfare of the community by increasing knowledge, attitudes, skills, behavior and abilities as well as utilizing resources through establishing policies, programs and activities. This community program is one of the solutions to deal with problems regarding the welfare and low economic level of the community. This article itself discusses optimizing the role of the Medan Estate Village government, Percut Sei Tuan sub-district, Deli Serdang Regency in community empowerment. The research method that the author uses is a qualitative research approach and uses a purposive sampling method, namely determining data sources by interviewing informants who are considered to know the most. The role of the national government and community administration in Medan has been optimally optimized.